Inspeksi Sambungan Rangka Mobil Listrik Tipe Tubular Space Frame Menggunakan Las GMAW dengan Cairan Liquid Penetrant - Satria Jati, Unggul; Prabowo, Dian; Dwi Hastuti, Hety; Van Gunawan, Leo (P3M Politeknik Negeri Cilacap, 2024)
Technological developments increasingly require humans to increase their competence and innovation. The process of making frames for electric cars is one of the innovations to produce a strong frame. The frame is the main and important part of a vehicle, because the components and passengers will support the frame. The connection between frame components uses GMAW welding, which is the process of joining metal materials by heating them until they reach their melting point. To obtain a frame that meets the criteria, it is necessary to carry out a testing process, this testing process is NDT testing (Non Destructive Test), namely testing the physical part of the material in a way that does not damage the test object. Meanwhile, the aim of this research is to inspect the electric car frame so as to find discontinuities in the GMAW welding results. The results of this research were that there were 22 samples that underwent the liquid penetrant test process, of the total samples according to ASME Section VIII Division 1 Mandatory Appendix 6 there were 14 specimens that were acceptable while 8 needed improvement in the connection process. After the repair or repair process has been carried out, the frame is declared fit for use.